Perfil das mulheres que realizam interrupções voluntárias da gravidez: um estudo transversal - Santos,Catarina Neves (2022)
Abstract Overview and Aims: The number of voluntary interruptions of pregnancy, despite its decreasing trend, remains with marked regional asymmetries. The profile of the populations that most perform voluntary abortion is not known. With this study, we aim to establish the profile of these women and analyse their temporal evolution, to build effective and targeted preventive measures. Study Design: Cross-sectional study. Population: Women who had a voluntary abortion in a district hospital between 2012-2018. Methods: We collected sociodemographic, gynaecological and obstetric data from the database of the voluntary abortion consultation. Statistical analysis was performed with SPSS®. Results: Most women who had a voluntary abortion were between 20 and 40 years old, were Portuguese, had a 3 rd cycle or secondary education, were single, had children, and were unemployed or had unskilled work. However, young women under 20 years old and immigrants were the ones with higher risk of voluntary interruption of pregnancy. Regarding women with a history of previous voluntary abortions, they tended to have more children and there was a greater proportion of immigrant and women with low education or professional qualification in this subgroup. Conclusion: Socio-economic frailty, which is more pronounced among young women, immigrants, and precarious workers, seems to be the main predisposing factor for voluntary interruptions of pregnancy. It is imperative to invest in sexual education and health literacy, improve access to family planning consultations and contraceptive methods and invest in closer and regular follow-up of these women at higher risk.